Analysis of a Compact Wideband Slotted Antenna for Ku Band Applications. (9th April 2014) - Ahsan, M. R.; Habib Ullah, M.; Mansor, F.; Misran, N.; Islam, T.
Abstract : The design procedure and physical module of a compact wideband patch antenna for Ku band application are presented in this paper. Finite element method based on 3D electromagnetic field solver has been utilized for the designing and analyzing process of proposed microstrip line fed modified E -H shaped electrically small patch antenna. After successful completion of the design process through various simulations, the proposed antenna has been fabricated on printed circuit board (PCB) and its characteristics have been studied. The parameters of the proposed antenna prototype have been measured in standard far-field rectangular shape anechoic measurement compartment. It is apparent from the measured antenna parameters that the proposed antenna achieved almost stable variation of radiation pattern over the entire operational band with 1380 MHz of - 10 dB return loss bandwidth. The maximum gain of 7.8 dBi and 89.97% average efficiency within the operating band from 17.15 GHz to 18.53 GHz ensure the suitability of the proposed antenna for Ku band applications.